The Factor Structure and Reliability of the Persian Version of the Children's Sleep Habits Questionnaire in Children with Autism Spectrum Disorder - Karamali Esmaili, Samaneh; Mousazade, Homeyra; Amini, Malek (Iranian Journal of Child Neurology, 2026)
Objectives: Sleep disturbance is a common difficulty in children with autism spectrum disorder that can affect daily functioning and quality of life. Research has established an association between the severity of autism and the severity of sleep problems. But the assessment and intervention in this issue are less noticed by therapists. This study aimed to investigate the psychometric properties of the Children’s Sleep Habits Questionnaire (CSHQ) including content validity, factor analysis, internal consistency, and test-retest reliability in children with autism aged 4–10 years. Materials and Methods: In this descriptive and cross-sectional study, 306 parents of children with autism were selected by convenience sampling. They answered the Persian version of the CSHQ. The content validity index and ratio were assessed through opinions of 11 autism experts. Confirmatory factor analysis was conducted. Cronbach's alpha coefficient was used for internal consistency, and the intraclass correlation coefficient was calculated for test-retest reliability. Data were analyzed by and LISREL 88 and SPSS 26. Results: The content validity index (0.81-1) and ratio (0.63–1) were confirmed. The confirmatory factor analysis results (RMSEA = 0.74; P < 0.001; Chi-Square =596.85; df = 224) confirmed the model obtained. The total Cronbach's alpha was 0.83. The intraclass correlation coefficient for the test-retest reliability was 0.90 in total and 0.82-0.91 for the domains of the questionnaire. Conclusion: The Persian version of CSHQ in children with autism has acceptable validity and reliability and can be used by autism therapists as a suitable tool in research and clinical practice.